2016
DOI: 10.1016/j.ijpsycho.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Shooting under cardiovascular load: Electroencephalographic activity in preparation for biathlon shooting

Abstract: This study explored the influence of sub-maximal cardiovascular load on electroencephalographic (EEG) activity preceding biathlon shooting. Frontal-midline theta and alpha power were examined to assess monitoring processes and cortical inhibition, respectively. Thirteen experienced biathletes (mean age: 17years; 5 males, 8 females) fired sets of five consecutive shots from the standing position at a 50-meter-distant target, under two fixed-order conditions: (i) at rest and (ii) immediately after 3-minute exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 30 publications
4
29
0
Order By: Relevance
“…In other words, the gating pattern became more intense just before the start of movement execution. Our finding replicates that of Gallicchio, Finkenzeller, et al () who observed a focal topography of alpha power prior to rifle shooting but not at rest. These findings help consolidate the argument that the alpha gating phenomenon observed in motor tasks is specific to preparation for movement.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In other words, the gating pattern became more intense just before the start of movement execution. Our finding replicates that of Gallicchio, Finkenzeller, et al () who observed a focal topography of alpha power prior to rifle shooting but not at rest. These findings help consolidate the argument that the alpha gating phenomenon observed in motor tasks is specific to preparation for movement.…”
Section: Discussionsupporting
confidence: 92%
“…Within the framework of the alpha gating-by-inhibition model (Jensen & Mazaheri, 2010), this result can be interpreted as deficient gating of cognitive resources across the cortex. In line with previous interpretations of the movement-related alpha gating phenomenon (Gallicchio et al, 2017;Gallicchio, Finkenzeller, et al, 2016), the weaker alpha gate observed for the random group reflects less psychomotor efficiency (Hatfield, 2018;Hatfield & Hillman, 2001) compared to the blocked group. These novel findings provide evidence that increased inhibition of cortical regions that are not involved with movement seems to be more important than increased activation of regions that are responsible for movement control.…”
Section: Target Variabilitysupporting
confidence: 87%
See 3 more Smart Citations